CERVICAL ISCHEMIC MYELOPATHY - Abdukadirova Dilfuza Tairdjanovna; Khaydarov Khakimjon Baxtiyor ogli (Journal of new century innovations, 2022)
Myelopathy (Greek myelos bone marrow, spinal cord + pathos suffering, disease) non-inflammatory, degenerative lesions of the spinal cord of various etiologies. Allocate vertebrogenic, atherosclerotic, carcinomatous, post-traumatic, metabolic, post-radiation myelopathy.